2021
DOI: 10.1002/jcp.30597
|View full text |Cite
|
Sign up to set email alerts
|

Insulin acts as an atypical KCNQ1/KCNE1‐current activator and reverses long QT in insulin‐resistant aged rats by accelerating the ventricular action potential repolarization through affecting the β3‐adrenergic receptor signaling pathway

Abstract: Insufficient-heart function is associated with myocardial insulin resistance in the elderly, particularly associated with long-QT, in a dependency on dysfunctional KCNQ1/KCNE1-channels. So, we aimed to examine the contribution of alterations in KCNQ1/KCNE1-current (I Ks ) to the aging-related remodeling of the heart as well as the role of insulin treatment on I Ks in the aged rats. Prolonged late-phase action potential (AP) repolarization of ventricular cardiomyocytes from insulin-resistant 24-month-old rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…In addition, the literature data have shown a correlation between reduced insulin sensitivity and heart dysfunction, at most, via an increase in the QT-interval (long-QT) not only in diabetic patients 28,29 but also in aged mammalians. 30,31 Therefore, we aimed to examine a possible correlation between aging and associated heart dysfunction, through contribution of long-QT, at least, via alterations in connexin statuses, including not only their protein expression levels but also their cellular localizations. So, here, we examined the contribution of changes in the expression levels of pCx43 and Cx43 as well as their cellular localization and distribution patterns in the left ventricular part of the heart from insulin-resistant elderly rats with an apparent long-QT in their surface ECGs (Aged-group; 24 months old).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the literature data have shown a correlation between reduced insulin sensitivity and heart dysfunction, at most, via an increase in the QT-interval (long-QT) not only in diabetic patients 28,29 but also in aged mammalians. 30,31 Therefore, we aimed to examine a possible correlation between aging and associated heart dysfunction, through contribution of long-QT, at least, via alterations in connexin statuses, including not only their protein expression levels but also their cellular localizations. So, here, we examined the contribution of changes in the expression levels of pCx43 and Cx43 as well as their cellular localization and distribution patterns in the left ventricular part of the heart from insulin-resistant elderly rats with an apparent long-QT in their surface ECGs (Aged-group; 24 months old).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, since heart weight/body weight measurement is not the gold standart in hyperthropy evaluation, we can still speculate that there might be compensatory heart hypertrophy in MetS animals in current study. Moreover, we demonstrated cardiac hypertrophy bu using echocardiography in MetS animals in our previous study [ 47 ]. Therefore, the higher blood pressure leves despite reduced contractile force can be related to compensatory hypertrophy in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the cg01647172 is mapped to the 5' untranslated region of the gene Pleckstrin Homology Domain Containing A1 (PLEKHA1) and is found hypomethylated in OCD patients. Likewise, we observed that the hypomethylated CpG cg00382572 position is assigned to the KCNQ1 gene coding for the Kcnq1 potassium channel, which is located in the pancreas and has been also associated with diabetes [24][25][26][27][28][29] . Finally, the cg19069918 is located near the gene TRPM8, which has been long studied as a cancer biomarker, particularly in pancreatic cancer 30 .…”
Section: Functional Annotationmentioning
confidence: 84%